The 'body' and Lady Wisdom (Proverbs 1-9) - Viviers, Hennie (Old Testament essays, 2005)
The personification of wisdom as Lady Wisdom in Proverbs 1-9, evokes quite juxtaposed appreciations. Some believe she is good news for women. She occupies an elevated position close to Yahweh, which is rather unheard of in patriarchal Israelite culture. Others are convinced that she ultimately serves mainly male hegemony and interests being so closely aligned with the (male) divinity. What is her true agency? Utilizing body criticism Lady Wisdom is analysed. Body constructs expose a society's deepest convictions and values. It is especially the 'regulatory body' (ideal, normative, paradigmatic) that becomes a society's cultural script or 'corporeal code', determining all others. Onto and 'into' this body-'text' is written a society's values, often hidden. The regulatory body of the time shaped Lady Wisdom primarily into an effective male-empowering mechanism, making her not an attractive model for modern politically active women.